(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the theoretical and methodological foundations of improving the methodology for developing students’ ecological competence based on cooperation between pedagogical disciplines, the methodological system for developing students’ ecological competence based on interdisciplinary cooperation, and the effectiveness of the methodology for developing students’ ecological competence based on interdisciplinary cooperation using the example of pedagogical disciplines, and its current need is comprehensively covered.